Consolidating democracy in Poland - Taras, Ray 1946- (Westview Press, 1995)
A comprehensive analysis of politics in a young European democracy, this book describes the principal features of Poland's democratic system - the political institutions, parties, elections, and leaders that have shaped the transition from communism. Recognizing that democratic consolidation requires economic development, Raymond Taras also considers Poland's economic performance under free-market rules as well as the related issues of privatization, foreign investment, trade, and integration into the global economy. His testing of theories of transition and development makes this text an important contribution to the comparative study of democratic consolidation.